Food-service industry: an overview of attributes that influences customers to repeat purchase intention / Nuramira Mohd. Yusop and Siti Munawarah Zakaria - Mohd. Yusop, Nuramira; Zakaria, Siti Munawarah (2010)
This research concerns on an overview of restaurant’s attributes that influence customer repeat purchase intention at restaurant. The term food industry is referring to the complex, global collective of diverse businesses that together supply much of the food energy consumed. The objectives of conducting this research are to identify the most influential restaurant’s attribute that lead to repeat purchase among the customer, to observe the most dominant attribute that lead customer repeat purchase base from gender differences and third is to examine the relationship between dependant variable (repeat purchase intention) and independent variables (place, price, good quality food, brand name and menu variety). Specifically this research had been done at Bujang Valley area, Kedah. A total of respondent of 278 were selected fill the sets of questionnaires. The data was analyzed with descriptive statistic, Independent group T-Test and Two-Way ANOVA of Statistical Package for Social Sciences (SPSS) version 16.0. The result shows that the most factor that influencing the customers to repeat purchase is price and male customers also tend to prefer price as the factor for them to repeat purchase in a restaurant. The next influential attribute is menu variety in which it can be as the additional criteria for a restaurant to attract customer to repeat purchase.